How Can Safety Nets Contribute to Economic Growth? - Alderman, Harold; Yemtsov, Ruslan (Oxford University Press on behalf of the World Bank, 2015)
The paper provides an up-to date and selective review of the literature on how social safety nets contribute to growth. The evidence is carefully chosen to show how safety nets have the potential to overcome constraints on growth linked to market failures, and is organized into four distinct pathways: i) encouraging asset accumulation by changing incentives and by addressing imperfections in financial markets caused by constraints in obtaining credit, and from information asymmetries; overcoming such failures helps households to invest into their human capital or productive assets; ii) failures in insurance markets especially in low income setting; safety nets are assisting in managing risk both ex post and ex ante; iii) safety nets are overcoming failure to create assets and other local economy complementary factors to household-level investments; iv) safety nets are shown to relax political constraints on policy. Safety nets have a dual objective of directly alleviating poverty through transfers to the poor and of triggering higher growth for the poor. However, the trade-off between the dual objectives of equity and growth is not eliminated by the potential for productive safety nets; this remains critical for designing social policies.